(3HdhZ GdCed aj af GdRLds - (3GHf MLI GdMehj , CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdGRQGQj, Jbj GdOjf GHf MLg,J (B837 (3g` s
(3ChdgG (B:s
(3hHYO aGf GdGOH LfS jUOb Ydi CfhGY YLjHg hafhf ZQjHI hdcf fYed gfG Hbhd GdbGFd (B:(3EPG cGf eOM aGdfSjH GdebOe s
(3BNQgG (B:s
(3heG ChQOJg ef GdeMGSf GdHOjYI ddaQjbjf , hbO SejJg HdhZ GdCed ai af GdRLd hdYeQi aEf SejJI gfG JWGHb GdeSei aZf GdWGdH de jHdZ Cgdg ef ZjQ gPG GdcJGH hdh WdH gPg GdeMGSf ef ZjQg JhGQJ Yfg HGdMLGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B126 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B254s
(3eUOQ GbJfGA GdCUd (B:s
(3dCMeOjI , JhfS (B(4467) s
Keywords: (3GdCOHs